Direct Numerical Optimisation of a Fuel Jet Pump Based on a Pseudo-Compressibility Method Using Characteristic Boundary Conditions - Veress, Arpad; Rohacs, Jozsef; Santa, Imre; Gausz, Tamas (Communications - Scientific letters of the University of Zilina, 2005)
The paper tries to give an overview of the latest industrial development of the Department of Aircraft and Ships at the Budapest University of Technology and Economics. The numerical investigation presented below based on Chorin’s pseudo-compressibility method is used to make the incompressible Euler equations artificially hyperbolic [1]. A less dissipative flux difference splitting method is evolved to solve governing equations. A low cost 4th order Runge-Kutta method is applied for time marching in pseudo space. Both extrapolated and characteristic type boundary conditions are examined and compared with each other in qualitative accuracy and convergence point of view. Using the described computational tool a direct numerical optimisation of a fuel jet pump is performed.